Orthodontics and Smile Correction in Teenagers-A Survey (Indian Journal of Forensic Medicine & Toxicology, 2020)
Orthodontics is a branch of dentistry that deals with diagnosis, prevention and correction of malpositionedteeth and jaws. Correction of malpositioned teeth is done by moving teeth and adjusting the underlyingbone with the help of certain devices. Ideal age for undergoing orthodontic treatment is between 8 to 14years. Orthodontics treatment is required for malocclusion of teeth to establish proper bite and to improveaesthetics. Malocclusion affects the individual self satisfaction, self confidence and causes emotional andmental disturbances. The aim of the study is to evaluate the awareness on orthodontics and smile correctionin teenagers. A cross sectional survey was conducted among teenagers to evaluate the awareness aboutorthodontics and smile correction in teenagers.. The study population in the study are the teenagers with asample size of 100. The questionnaire consisted of 20 questions and was shared to teenagers using onlinesurvey platform. 80% of the participants were aware about orthodontics and 20% were not aware. 41% ofthe respondents have worn braces before and 59% have not. 27% of the participants felt that their teethalignment is perfect, 29% did not feel that way and 34% said almost perfect. 75%of the participants feel thatorthodontic treatment is necessary for malocclusion of teeth, 7%did not feel as necessary and 18% maybefelt as necessary. From the results obtained, we can include that the moderate level of awareness is seen inteenagers about orthodontic treatment. More awareness is required as treatments are more effective whendone at an early age.
Keywords: Orthodontics; smile correction; awareness; teenagers; orthodontic treatment; malocclusion